Optimizing Real-Time Weather Data and Information Services with Frameworks and Application Programming Interfaces - Ihsan; Fathur Zaini Rachman; Dwi Lesmideyarti; Mikail Eko Prasetyo; Nur Yanti (Universitas Medan Area, 2026)
The need for fast, accurate, and secure weather information is a major challenge in BMKG public services. This research aims to develop a web-based information system capable of presenting real-time weather, climate, and flight forecast data, as well as supporting transaction services and digital data distribution at the BMKG Balikpapan Meteorological Station. The method employed is Research and Development (R&D), utilizing a Waterfall model in conjunction with the Network Development Life Cycle (NDLC). The research stages include needs analysis, system design, implementation using a web framework, and integration of Application Programming Interface (API) for real-time data synchronization. The system utilizes PostgreSQL as a database and the SMTP protocol for sending verification emails. Key features developed include login and registration with layered verification, uploading proof of payment, and automatic sending of documents to user emails. With a responsive interface design and good data integration, this system improves the efficiency, security, and transparency of public services. The results of Black Box Testing on six items were declared successful. Additionally, system quality testing, conducted among 17 respondents through six questions using a Likert scale, yielded an average of 95.08%, indicating a very good category. This system supports the digital transformation. These findings imply that the developed system has the potential to be adapted to other sectors, such as health and agriculture, to support more efficient and secure digitalization of public services